Religious Moderation Agency Among Religious Minorities: A Narrative Inquiry into Muslim Experiences in Humbang Hasundutan - Musdalifah Putri (Yayasan Bayt Shufiya Nusantara, 2026)
This study aims to examine the construction of religious moderation among a Muslim minority community in Pearaja Matiti II Village, Humbang Hasundutan Regency, North Sumatra, Indonesia. The study focuses on identifying the role of social capital, the negotiation of interreligious relations, and the contribution of religious actors in fostering and sustaining social harmony within a multicultural society. Employing a qualitative approach with a case study design, data were collected through observations, in-depth interviews, and documentation involving religious leaders, village authorities, and community members. The data were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings reveal that religious moderation within the Muslim minority community is socially constructed through the interaction of non-formal religious education, trust-based social capital and mutual cooperation, interreligious reciprocity, and the leadership of religious figures and local government authorities. Non-formal Islamic education functions as a medium for reproducing moral values that encourage social openness, while reciprocal relations between Muslim and Christian communities are manifested through collective participation in religious, social, and humanitarian activities. Furthermore, religious leaders and local authorities serve as agents of moderation who bridge differences and strengthen social cohesion. This study concludes that religious moderation among Muslim minority communities is a social construct shaped by the synergy between a strong religious identity and openness to diversity.